Safety and Efficacy of Banaba–Moringa oleifera–Green Coffee Bean Extracts and Vitamin D3 in a Sustained Release Weight Management Supplement. (12th February 2016) - Stohs, Sidney J.; Kaats, Gilbert R.; Preuss, Harry G.
Abstract : This 60‐day, 30‐subject pilot study examined a novel combination of ingredients in a unique sustained release (Carbopol matrix) tablet consumed twice daily. The product was composed of extracts of banaba leaf, green coffee bean, and Moringa oleifera leaf and vitamin D3. Safety was assessed using a 45‐measurement blood chemistry panel, an 86‐item self‐reported Quality of Life Inventory, bone mineral density, and cardiovascular changes. Efficacy was assessed by calculating a body composition improvement index (BCI) based on changes in dual energy X‐ray absorptiometry measured fat mass (FM) and fat‐free mass (FFM) as well as between the study group (SG) and a historical placebo group. No changes occurred in any blood chemistry measurements. Positive changes were found in the Quality of Life (QOL) inventory composite scores. No adverse effects were observed. Decreases occurred in FM ( p  = 0.004) and increases in FFM ( p  = 0.009). Relative to the historical placebo group, the SG lost more FM ( p  < 0.0001), gained more FFM ( p  = <0.0001), and had a negative BCI of −2.7 lb. compared with a positive BCI in the SG of 3.4 lb., a 6.1 discordance ( p  = 0.0009). The data support the safety and efficacy of this unique product and demonstrate importance of using changes in body composition versus scale weight and BMI. © 2016 The Authors Phytotherapy Research Published by John Wiley & Sons Ltd